Prospective Directions for the Modernization of Control Tools Load Regime in the United Energy System of Ukraine - Lenchevsky, Yevhen; Godun, Oleg (General Energy Institute of the National Academy of Sciences of Ukraine, 2023)
Considered a promising possibility in the system of dispatching control of the load mode of the United energy system of Ukraine to ensure the processes of regulating the generating capacities of NPP stations. The new direction of construction of control systems using the United energy system of Ukraine mode will make it possible to abandon too expensive means of maneuverable generation, such as the construction of reserve stations with highly maneuverable TPPs that have high-speed start-up characteristics, as well as frequency control support systems using powerful storage batteries. Instead, it is proposed to use powerful automatically controlled electric boilers, previously included in the means of regulating the load regime of the combined energy system. This will contribute to the further development of the generating capacity of nuclear power plants, wind power plants, and thermal power plants, as well as to the resolution of issues related to ensuring the stability and sustainability of the combined power system.